Variable Exponent Function Spaces related to a Sublinear Expectation. (13th January 2020) - Xu, Bochi
Abstract : In this paper, variable exponent function spaces L p ·, L b p ·, and L c p · are introduced in the framework of sublinear expectation, and some basic and important properties of these spaces are given. A version of Kolmogorov's criterion on variable exponent function spaces is proved for continuous modification of stochastic processes.